Autophagy-related MicroRNAs in chronic lung diseases and lung cancer. (September 2020) - Rezaei, Samaneh; Mahjoubin-Tehran, Maryam; Aghaee-Bakhtiari, Seyed Hamid; Jalili, Amin; Movahedpour, Ahmad; Khan, Haroon; Moghoofei, Mohsen; Shojaei, Zahra; R Hamblin, Michael; Mirzaei, Hamed
Abstract: Chronic lung disease has become a leading cause of death in recent years. Despite several attempts to discover and develop new therapeutic approaches, patients often suffer a poor quality of life, and are faced with an increased risk of developing lung cancer. Lung cancer often occurs as an end-stage after years of chronic lung disease. An increased understanding of the pathophysiology of chronic lung disease may be obtained from studying the role of autophagy in its initiation and progression. MicroRNAs (miRNAs) play a critical role in the modulation of autophagy, and their deregulation could be associated with the initiation and progression of several chronic lung diseases. Herein, we documented that up/down regulation of miRNAs can activate or inhibit autophagy in chronic lung diseases including lung cancer. Therefore, theses miRNAs could be a promising therapeutic tool for lung cancer specially in drug-resistance lung cancer cells.